Pengaruh Intensitas Aset Tetap,Komisaris Independen,dan Kepemilikan Institusional Terhadap Tax Avoidance pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Nicholas Phandi; Lauw Tjun Tjun (Jurnal Akuntansi, 2021)
Abstract This study aims to determine the effect of the intensity of fixed assets, independent commissioners, and institutional ownership on tax avoidance in banking companies listed on the IDX. The research sample is 25 banking companies. The results of this study indicate that the intensity of fixed assets and independent commissioners has no effect on tax avoidance, while institutional ownership has an influence on tax avoidance. This research was conducted to contribute to banking companies so as not to evade taxes, because it will have an impact on state revenues. Keywords: Intensity Of Fixed Assets, Independent Commissioners, Institutional Ownership, and Tax Avoidance